2012
DOI: 10.1515/cclm-2012-0097
|View full text |Cite
|
Sign up to set email alerts
|

Human epididymis protein 4 (HE4) in benign and malignant diseases

Abstract: Background: Human epididymis protein 4 (HE4) is described as a useful new biomarker in ovarian cancer. As HE4 is neither tumor nor organ specifi c, we intensively investigated the occurrence of this protein in female and male patients with various benign and malignant diseases in order to avoid misinterpretation and to identify potential additional clinical relevance. Methods:We retrospectively investigated HE4 (ARCHITECT ® , Abbott Diagnostics, US) in the sera of 205 healthy individuals, 654 patients with ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 19 publications
2
89
0
2
Order By: Relevance
“…Generally, HE4 levels in healthy women are higher than those in healthy men (median 26.2 pM vs. 40.4 pM) presumably due to the HE4 expression in woman's reproductive organs. In both sexes, the HE4 levels appear to increase with age [36]. In a study by Bolstad et al, HE4 was measured in 1591 subjects comprised of 801 women and 790 men of age 18-86 years from the Nordic Reference Interval Project Bio-bank and Database.…”
Section: Variation Of He4 Levels With Demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, HE4 levels in healthy women are higher than those in healthy men (median 26.2 pM vs. 40.4 pM) presumably due to the HE4 expression in woman's reproductive organs. In both sexes, the HE4 levels appear to increase with age [36]. In a study by Bolstad et al, HE4 was measured in 1591 subjects comprised of 801 women and 790 men of age 18-86 years from the Nordic Reference Interval Project Bio-bank and Database.…”
Section: Variation Of He4 Levels With Demographic Factorsmentioning
confidence: 99%
“…Hertlein et al compared serum HE4 concentrations in patients with several benign gynecological diseases such as benign cervical diseases, cystadenoma, leiomyoma, bleeding disorder, endometriosis, functional ovarian cyst, and inflammation diseases [36]. They found that women with inflammation diseases had the highest median values of serum HE4 (median 67.6 pM).…”
Section: Inflammatory Diseasementioning
confidence: 99%
“…HE4 was found to offer a better diagnostic performance than CA125 for distinguishing between benign and malignant pelvic masses (Holcomb et al, 2011;Zheng and Gao, 2012;Chung et al, 2013). Regardless of its beneficial characteristics, similar to classic tumor markers (Trapé et al, 2011), HE4 has some limitations in the detection of tumors, where its level may be elevated in benign diseases without evidence of malignancy (Hertlein et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[14] обнаружили повышенную экс-прессию НЕ4 не только в опухолевой ткани РЯ, но и не-которых других опухолей, в том числе и в РЭ. Результаты оценки НЕ4 как потенциального ОМ для РЭ противоре-чивы [7,[15][16][17][18]. В 2008 г. R. Moore и соавт.…”
unclassified
“…[18]. В других публикациях приводятся данные о меньшей чувствительности НЕ4 для РЭ [16,17], и даже показано преимущество СА125 (50% против 28% -для НЕ4) [15].…”
unclassified